A simple method for Ge incorporation to enhance performance of low temperature and non-vacuum based CZTSSe solar cells. (1st April 2022) - Punathil, Prabeesh; Artegiani, Elisa; Zanetti, Solidea; Lozzi, Luca; Kumar, Vikash; Romeo, Alessandro
Highlights: Selenization treatment of CZTS is done at low temperature: 450 °C. Chlorine based compounds are successful for Na, K and Ge inclusion. Ge with Se generates GeSe, Ge inclusion limits Se incorporation in CZTS. Ge-devices show a higher carrier concentration and lower compensating defects. Ge-CZTSSe based devices have an almost 25% increase in efficiency. Abstract: Despite the slow efficiency development, Cu2 ZnSn(S, Se)4 still is a promising absorber material for solar cells for its easy and low cost way of fabrication and the abundance of its elements. Similarly, also CdTe faced a long period when the record efficiency would not improve over 16.5% until a different paradigm was introduced. CZTSSe, compared to other absorbers, has the advantage that can be successfully made by solution-based growth techniques which are unique for their low cost. However this is meaningful only if selenization process is not done at high temperatures and without complicated processes. So we have optimized an easy, low cost, non-vacuum fabrication process for Cu2 (Zn, Sn)(S, Se)4 thin-film absorber layers by spin coating of precursor and subsequent lower temperature selenization. A precursor solution is deposited on a Mo coated glass and the stack is then annealed below 450 °C in Se atmosphere and without the application of toxic hydrazine. With this process, we have already presented efficiencies of around 5.5%, but in this work, we introduce a simple impurity inclusion process by treating the surface of the precursor film with chlorine-based compound containing either Na, K or Ge. This allows to improve the open circuit voltage and the current density, with an increase in efficiency of 25% compared to the non-treated sample. The structural modifications are addressed by X-ray diffraction, Raman spectroscopy, atomic force microscopy and scanning electron microscopy. Current-voltage, capacitance-voltage and drive level capacitance profiling are used to analyse performance and defect density in the finished devices.